Instructors as communication strategists: using multimodal communication to implement a new course policy on assignment extension due dates - Ruesch, Joseph M.; Sarvary, Mark A. (Frontiers in Education, 2025)
This study examines the implementation process and impact of a new course policy, the Emergency Button (EB), that was introduced to enhance the previously established penalty-free assignment extension policy (EWP) in a large introductory course. While the previously published EWP provided a short-term assignment extension, the EB allows students to submit one assignment even after the extension due date. The findings reveal that students without the EB could have faced a 5% grade reduction due to the missed assignment. While the EWP use was higher than in the semester when it was introduced, only 15% of the students chose to use the novel EB, and half of those did so because it allowed them to reprioritize other academic tasks. A larger percentage of first-generation college students benefited from the EB policy than others (27% vs. 13%). A comprehensive communication strategy was developed to ensure successful policy implementation. The strategy included information dissemination through the syllabus, lectures, labs, peer instruction, course website, and infographics. While the syllabus was the primary source of information, other oral and visual channels were necessary to improve the clarity about the new course policy. Increasing the number of communication channels decreased the confusion about the extension policies. Despite using the same communication strategy, students indicated less confusion about the established EWP policy compared to the novel EB policy, highlighting the additional challenges associated with introducing new pedagogical strategies. This study underscores the significance of strategic communication in implementing new course policies, suggesting that using a blend of visual and oral communication modalities engages students more successfully.